The wrong marquess - Lorret, Vivienne (Lorret, Vivienne. Mating habits of scoundrels., 2021)
Considered “London's Most Elusive Bachelor,” Brandon, Marquess of Hullworth, finally finds a woman worth his time in Ellie Parrish, a quirky, opinionated lady who drives him absolutely wild, but she believes she's in love with someone else.